2015
DOI: 10.1503/jpn.140126
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of IL-6 in the cerebrospinal fluid of patients with chronic schizophrenia — significance for activation of the kynurenine pathway

Abstract: IntroductionThe role of immune activation in schizophrenia has received increasing interest in recent years. Epidemiological studies have shown that infections and autoimmune diseases are clin ic ally important risk factors for the development of schizo phrenia. [1][2][3] Furthermore, a recent study integrating results from a meta analysis of genome wide association studies in schizophrenia found that the most significant changes were observed in genetic loci related to the immune system. 4 Also, patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(53 citation statements)
references
References 52 publications
4
45
0
1
Order By: Relevance
“…The bead-based Luminex® (Bio-Rad Laboratories, Inc.) platform has been used for CSF sample to measure 8 cytokine levels in 43 patients with BD or MDD ( Haroon et al, 2016 ), while the immunoassay-based protein array multiplex system has been used for CSF samples to measure 10 cytokine levels in 30 patients with BD and 30 controls ( Soderlund et al, 2011 ). The electro-chemiluminescence-based V-plex® (MesoScale Discovery) platform has also been used for CSF samples to measure 10 cytokine levels in 23 patients with chronic schizophrenia and 37 controls ( Schwieler et al, 2015 ), 5 cytokine levels in 11 patients with recent-onset schizophrenia and 12 controls ( Coughlin et al, 2016 ), 2 cytokine levels in 19 patients with current depression and 67 subjects without depression among older women ( Kern et al, 2014 ), and 11 cytokine levels in 16 patients with schizophrenia and 15 with affective disorders ( Maxeiner et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The bead-based Luminex® (Bio-Rad Laboratories, Inc.) platform has been used for CSF sample to measure 8 cytokine levels in 43 patients with BD or MDD ( Haroon et al, 2016 ), while the immunoassay-based protein array multiplex system has been used for CSF samples to measure 10 cytokine levels in 30 patients with BD and 30 controls ( Soderlund et al, 2011 ). The electro-chemiluminescence-based V-plex® (MesoScale Discovery) platform has also been used for CSF samples to measure 10 cytokine levels in 23 patients with chronic schizophrenia and 37 controls ( Schwieler et al, 2015 ), 5 cytokine levels in 11 patients with recent-onset schizophrenia and 12 controls ( Coughlin et al, 2016 ), 2 cytokine levels in 19 patients with current depression and 67 subjects without depression among older women ( Kern et al, 2014 ), and 11 cytokine levels in 16 patients with schizophrenia and 15 with affective disorders ( Maxeiner et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that pro-inflammatory cytokines were increased in both serum and cerebrospinal fluid (CSF) in first-episode schizophrenia [163][164][165], and patients with chronic schizophrenia [166]. Postmortem studies have also shown inflammatory markers in the dorsolateral prefrontal cortex, and microglial activity and microglial cellular density were all increased in schizophrenic patients [165,[167][168][169]. The pro-inflammatory cytokines increase PLA2 activity and breakdown of membrane phospholipids in schizophrenic patients [38,170].…”
Section: Modulation Of Neuro-inflammation In Schizophreniamentioning
confidence: 99%
“…IL-6 has been suggested to mediate the microglial-induced inflammatory response to neurogenesis (17). Previous data showed higher serum and cerebrospinal fluid (CSF) IL-6 levels in SZ patients and increased mRNA expression of IL-6 in post-mortem brain of SZ patients (1820). High sensitivity CRP (hsCRP) is a nonspecific marker of inflammatory state and is mainly synthesized by hepatocytes in response to proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%